2017
DOI: 10.5194/bg-14-2979-2017
|View full text |Cite
|
Sign up to set email alerts
|

A numerical analysis of biogeochemical controls with physical modulation on hypoxia during summer in the Pearl River estuary

Abstract: Abstract.A three-dimensional (3-D) physicalbiogeochemical coupled model was applied to explore the mechanisms controlling the dissolved oxygen (DO) dynamics and bottom hypoxia during summer in the Pearl River estuary (PRE). By using the numerical oxygen tracers, we proposed a new method (namely the physical modulation method) to quantify the contributions of boundary conditions and each source and sink process occurring in local and adjacent waters to the DO conditions. A mass balance analysis of DO based on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 31 publications
3
53
1
Order By: Relevance
“…The total depositional flux of POC (including phytoplankton and nonliving POC) into sediment is 7.00 × 10 10 mol C year −1 , which is higher than the POC input from the river (5.59 × 10 10 mol C year −1 ). The deposition also results in high sediment oxygen demand in summer (Wang et al, ) and increases the DIC flux from the pore water of sediment to the overlying water in the PRE as mentioned earlier. The death of phytoplankton contributes 2.33 × 10 10 mol C year −1 of POC annually, which supports a relatively smaller part of the deposition of nonliving POC (with a maximum of 35.7%) compared to the deposition of terrestrial POC.…”
Section: Resultsmentioning
confidence: 87%
“…The total depositional flux of POC (including phytoplankton and nonliving POC) into sediment is 7.00 × 10 10 mol C year −1 , which is higher than the POC input from the river (5.59 × 10 10 mol C year −1 ). The deposition also results in high sediment oxygen demand in summer (Wang et al, ) and increases the DIC flux from the pore water of sediment to the overlying water in the PRE as mentioned earlier. The death of phytoplankton contributes 2.33 × 10 10 mol C year −1 of POC annually, which supports a relatively smaller part of the deposition of nonliving POC (with a maximum of 35.7%) compared to the deposition of terrestrial POC.…”
Section: Resultsmentioning
confidence: 87%
“…). The total bacterial respiration in the bottom mixed layer is estimated to be h BML R C = 7.38 g m −2 d −1 with h BML = 11.9 m. The value of SOD at the mooring site C is ~ 0.6 g m −2 d −1 (Wang et al ). In a word, all DO losses in the bottom mixed layer are 9.03 g m −2 d −1 , whereas the DO supply only by the horizontal advection from shelf benthic waters is 9.89 g m −2 d −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the coastal hypoxia is forecast to increase owing to the combined effects of continued spread of coastal eutrophication and global warming largely associated with human activities (Diaz and Rosenberg ; Vaquer‐Sunyer and Duarte ). More than 400 coastal systems of hypoxia (termed “dead zone”) have been identified, with a total area of more than 245,000 km 2 (Diaz and Rosenberg ), e.g., Gulf of Mexico (Rabalais et al ; Zhang et al ), Chesapeake Bay (Hagy et al ; Murphy et al ), Lower St. Lawrence Estuary (Bourgault et al ; Lefort et al ), Yangtze River (Changjiang) Estuary (Chen et al ; Wei et al ), and Pearl River (Zhujiang) Estuary (Yin et al ; Luo et al ; Wang et al ). While it is generally accepted that this increase was the result of increased anthropogenic nutrient loads to the estuaries or coastal ocean, studies that attempt to statistically relate the inter‐annual variations in hypoxic volume to nutrient loading often fail to explain the majority of the variability (Hagy et al ; Murphy et al ; Scully , ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That would be an explanation for the negative correlation (p<0.05) between NH 4 and O 2 in SL (Table 3). Wang et al (2017) reported that re-aeration and sediment oxygen demand were more important than photosynthesis and water column respiration as counterbalanced coupled processes affecting the near-bottom DO concentration in the shallow estuary. Re-aeration of deep waters in the MLs is not expected in summer (Vilibić et al 2010).…”
Section: Discussionmentioning
confidence: 99%